A Teacher Self-Assessment of Culturally Relevant Practice to Inform Educator Professional Development Decisions in MTSS Contexts. (March 2023) - Fallon, Lindsay M.; Cathcart, Sadie C.; Johnson, Austin H.; Minami, Takuya; O'Keeffe, Breda V.; DeFouw, Emily R.; Sugai, George
When students require support to improve outcomes in a variety of domains, educators provide youth with school-based intervention. When educators require support to improve their professional practice, school leaders and support personnel (e.g., school psychologists) provide teachers with professional development (PD), consultation, and coaching. This multi-study article describes how the Assessment of Culturally and Contextually Relevant Supports (ACCReS) was developed with the purpose of assessment driving intervention for teachers in need of support to engage in culturally responsive practice. Items for the ACCReS were created via a multi-step process including review by both expert and practitioner panels. Then, results of an exploratory factor analysis with a national sample of U.S. teachers ( N = 500) in Study 1 yielded three subscales. A confirmatory factor analysis conducted with a separate sample of teachers ( N = 400) in Study 2 produced adequate model fit. In Study 3, analyses with another final sample of teachers ( N = 99) indicated preliminary evidence of convergent validity between the ACCReS and two measures of teacher self-efficacy of culturally responsive practice. Data from the ACCReS can shape the content of educator intervention (e.g., PD) and promote more equitable student outcomes for youth.